Professional Psychological Help-Seeking in a Global and Indonesian Overview: A Bibliometric Analysis - Saniatuzzulfa, Rahmah; Hartini, Nurul; Andriani, Fitri (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Research on the search for professional psychological help has gained increasing attention in recent years. However, comprehensive analyses of trends and thematic developments within this field remain limited. Objective: This study aims to conduct a bibliometric analysis of the scientific literature on seeking professional psychological help and to map the research landscape.  Methods: Researchers performed a bibliometric data analysis using VOSviewer, based on data retrieved from the Scopus database between 2015 and 2024. This analysis involved creating visual maps based on the co-occurrence of keywords and thematic clustering. Results: A total of 1,522 documents were identified, with a significant increase in publications in 2024. PLOS ONE emerged as the journal with the highest number of publications. The United States contributed the largest number of publications. Conclusion: Network analysis revealed seven major research clusters, highlighting interconnected themes across studies. Emerging areas for future research include mental health professionals, psychological help-seeking behavior, help-seeking intentions, and service utilization. Additionally, key influencing variables such as mental health literacy, peer support, and self-stigma were identified as potential focal points for further investigation. These findings provide a comprehensive overview of the field and offer valuable insights for advancing research and practice in professional psychological help-seeking.